The evaluation of the relation between dynamic hip screw positions and its failure in unstable femur fractures. Issue 3 (27th May 2021) - Celik, Talip; Mutlu, Ibrahim; Ozkan, Arif; Kisioglu, Yasin
ABSTRACT: In this study, effects of the Dynamic Hip Screw (DHS) positions on its failure are investigated in unstable femur fracture using Finite Element Analysis (FEA). The failures of DHS were emphasised in the latest several case studies. In order to create 3D computerised models, the unstable femur fractures were generated in the trochanteric region of the femur obtained from Computerised Tomography Images. The DHS model in 3D CAD form was placed in nine different positions into the fractured femur. Two different Tip-Apex distances (TAD) (20 and 25 mm) were used for each DHS positions. In the FEA, muscles and body forces were applied to the femur according to the maximum value based on regular walking. The best position and TAD value were determined according to the von Mises stresses calculated on the DHS. The FEA calculation showed that the minimum stress value was obtained on the DHS placed in the middle and superior regions of femur head. Higher TAD value (25 mm) were decrease the von Mises stresses of the DHS. In conclusion, the calculated results suggest that the best DHS position is in the spherical centre of the femur head considering the failures of both femur and DHS together.